2017
DOI: 10.1159/000480081
|View full text |Cite
|
Sign up to set email alerts
|

Association between Allergies and Hypercholesterolemia: A Systematic Review

Abstract: Background: There is controversy in the literature regarding the potential relationship between atopic predisposition (AP) and serum cholesterol levels. To this purpose, we reviewed human studies that investigated this possible link. Methods: Following PRISMA guidelines, a literature search of PubMed and Science Direct for peer-reviewed journal articles in English from January 2003, with updates through to August 2016, was conducted. Relevant publications were reviewed that included pediatric and adult populat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2018
2018
2025
2025

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 47 publications
0
4
0
Order By: Relevance
“…12 Research suggests a link between cholesterol and the adaptive immune system, as both have the same immunological pathways involving Th1 toTh2 switch, an increase in Th2 related IgG1 and IgE release, and elevation of pro-inflammatory Th2 cytokines release such as IL-4. 13 Numerous research investigated the association between dyslipidemia and allergic diseases. Fessler et al 14 demonstrated the relationship between total cholesterol (TC) level and atopy in children 6-17 years of age.…”
Section: Introductionmentioning
confidence: 99%
“…12 Research suggests a link between cholesterol and the adaptive immune system, as both have the same immunological pathways involving Th1 toTh2 switch, an increase in Th2 related IgG1 and IgE release, and elevation of pro-inflammatory Th2 cytokines release such as IL-4. 13 Numerous research investigated the association between dyslipidemia and allergic diseases. Fessler et al 14 demonstrated the relationship between total cholesterol (TC) level and atopy in children 6-17 years of age.…”
Section: Introductionmentioning
confidence: 99%
“…For this reason, our finding that reduced bilirubin increases the incidence of asthma is novel and elucidates scope for further research. Total cholesterol levels have also been found to exhibit significant differences in the present study, and some studies have examined the correlation between cholesterol and allergies [ 31 , 32 ]. However, there remains controversy regarding the relationship between allergies and serum cholesterol levels, so we did not perform further analysis.…”
Section: Discussionmentioning
confidence: 52%
“…Above that, we were able to identify a direct contribution of alterations in the lipid metabolism to both the risk for contact allergy and hay fever. This is of interest since previous studies have not yet allowed for a clear valuation of this association mostly due to the lacking assessment of potential influencing factors [ 18 ]. Consistent with a higher proportion of hyperlipidaemia in contact allergy in comparison to the respective control group, we found a significant association with the participants’ dietary fat intake.…”
Section: Discussionmentioning
confidence: 99%